Xanthomonas citri subsp. citri requires a polyketide cyclase to activate the type III secretion system for virulence - Shuying Zhu; Siyu Wu; Yanmin Liu; Zaibao Zhang; Huasong Zou (BMC Microbiology)
Abstract Background Xanthomonas citri subsp. citri is the causal agent of citrus canker, which causes substantial losses in citrus production. Here, we report the role of a polyketide cyclase (PKC) on the virulence in X. citri subsp. citri. Methods The structure of PKC was precisely predicted using Alphafold3. Promoter GUS fusion constructs and real-time quantitative reverse transcription (qRT-PCR) were employed to study the pattern of expression of the polyketide gene. A deletion mutation was created to explore the role of PKC in virulence and metabolic change. Results The PKC was determined to have a signal peptide, a START/RHO_alpha_C/PITP/Bet_v1/CoxG/CalC (SRPBCC) domain, and a GyrI-like small molecule binding domain. The expression of the PKC gene was induced in planta, as well as under stress by CuSO4 and SDS. An in-frame deletion mutation resulted in a loss of virulence on the citrus hosts, which was restored by the SRPBCC domain. Furthermore, there as a remarkable reduction in the expression of type III genes, such as hrpG and hrpX. In the mutant carrying the pkc deletion, ketoleucine and acetone cyanohydrin were downregulated, and four metabolites, including d-ribose, creatine, polyoxyethylene dioleate, and cohibin C, were upregulated. Conclusions The overall data indicate that the PKC affects bacterial virulence by modulating the type III secretion system, possibly through the biosynthesis of particular metabolites.